2000
DOI: 10.1111/j.1749-6632.2000.tb05498.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Pharmacology in Pregnant Women and Their Newborns

Abstract: The physiologic changes of pregnancy have an impact on antiretroviral pharmacokinetic parameters, but the effect is generally not of sufficient magnitude to warrant alterations in dosing. Although administration of oral zidovudine during labor may not provide equivalent serum drug exposure as with continuous intravenous infusion, the clinical relevance of the difference is unknown. Nevirapine is well absorbed during labor, and sufficient drug for prophylaxis against perinatal transmission crosses the placenta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…FTC is primarily excreted by the kidney by both glomerular filtration and tubular secretion, with 86% recovery of the dose achieved in urine, as described in the full prescribing information for Truvada (http://www.gilead.com/pdf/truvada_pi.pdf). During pregnancy, renal plasma flow increases by 25 to 50% and glomerular filtration rate by 50%, which should have enhanced FTC elimination (13). The lowest FTC clearance increase in the PATCG/ IMPAACT P1026 study (23.3 liters/h versus 28.0 liters/h in our study) may be due the sampling time during pregnancy (third trimester versus the day of delivery in our study).…”
Section: Discussionmentioning
confidence: 55%
“…FTC is primarily excreted by the kidney by both glomerular filtration and tubular secretion, with 86% recovery of the dose achieved in urine, as described in the full prescribing information for Truvada (http://www.gilead.com/pdf/truvada_pi.pdf). During pregnancy, renal plasma flow increases by 25 to 50% and glomerular filtration rate by 50%, which should have enhanced FTC elimination (13). The lowest FTC clearance increase in the PATCG/ IMPAACT P1026 study (23.3 liters/h versus 28.0 liters/h in our study) may be due the sampling time during pregnancy (third trimester versus the day of delivery in our study).…”
Section: Discussionmentioning
confidence: 55%
“…Marzolini et al (16) also noted that maternal concentrations of protease inhibitors and nevirapine measured at delivery were lower than those observed in a general HIV-infected population and suggested that the decrease in plasma levels resulted from the nonspecific stimulation of general metabolism and enzyme expression level. Mirochnick et al (18) reported that women in labor given nevirapine demonstrated an increase in nevirapine halflife and a decrease in bioavailability. In our study, low nelfinavir and M8 concentrations at delivery could be explained by a decrease in bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…In general, plasma drug levels are lower during pregnancy than postpartum [8][9][10][11][12][13][14]. However, it is unclear whether lower concentrations induce virologic failure, increase MTCT, or cause more frequent treatment changes.…”
Section: Introductionmentioning
confidence: 96%